Pengaruh Pembelajaran Saintifik Terhadap Kemampuan Berpikir Kritis Anak Usia Dini - Marlen Bara Lay; Delti Fallo; Feti Hendrina Oematan; Nifren T Talan; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Early childhood education serves as a crucial stage for developing critical thinking skills as a 21st-century competency. This study aims to determine the influence of scientific learning on the critical thinking abilities of children aged 4-5 years. The research method is quantitative with an ex-post facto approach. The sampling technique used total sampling, namely 20 children aged 4-5 years at PAUD Bait' el Naimata, Kupang City. The data collection technique uses a Likert scale questionnaire for scientific learning (based on Mauriz et al., 2023; reliability 0.723) and an assessment rubric for critical thinking (based on Facione, 2011; reliability 0.705). The data analysis technique is simple linear regression with SPSS 26.0. The results of these findings show that scientific learning has a positive and significant effect on the critical thinking abilities of children aged 4-5 years by 20.7% (R Square = 0.207; p = 0.000 < 0.05), which means that the better the application of scientific learning, the greater the critical thinking abilities of young children. It is hoped that PAUD teachers will implement scientific learning optimally through the stages of observing, asking, trying, reasoning and communicating, as well as involving parents to improve the development of children's critical thinking.